1987
DOI: 10.1111/j.1365-2125.1987.tb03215.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the partial agonist activity of Ro 31‐1118, flusoxolol and pindolol in man.

Abstract: 1. The effects of single oral doses of three beta‐adrenoceptor partial agonists (Ro 31‐1118, flusoxolol and pindolol), two beta‐adrenoceptor antagonists (propranolol and atenolol), two beta‐adrenoceptor agonists (salbutamol and prenalterol) and placebo on sleeping heart rate, quality of sleep, supine heart rate, exercise heart rate, blood pressure, forearm blood flow and finger tremor were studied in eight healthy male volunteers. 2. Sleeping heart rate was increased by Ro 31‐ 1118, flusoxolol, pindolol, salbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…It is well known that in humans, the autonomic activity shows a circadian rhythm with an increase in parasympathetic activity during the night and a prevalence of sympathetic activity during the day. Therefore, the sleep period is characterized by a low level of sympathetic dominance, and the parasympathetic influence could reduce the heart rate, which reaches its lowest point after 5–6 hours of sleep (53,54). Thus, it is possible that HRV indices collected at evening/nighttime while sleeping may not be representative of day‐time HRV.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that in humans, the autonomic activity shows a circadian rhythm with an increase in parasympathetic activity during the night and a prevalence of sympathetic activity during the day. Therefore, the sleep period is characterized by a low level of sympathetic dominance, and the parasympathetic influence could reduce the heart rate, which reaches its lowest point after 5–6 hours of sleep (53,54). Thus, it is possible that HRV indices collected at evening/nighttime while sleeping may not be representative of day‐time HRV.…”
Section: Discussionmentioning
confidence: 99%
“…The HRV parameters were compared between the two doses of celiprolol alone, and when celiprolol was co-administered with propranolol 160 mg or atenolol 50 rag. The selectivity and dose-dependence of the partial agonist activity of agents acting at the/3a-or #2-adrenoceptor can be assessed from the sleeping heart rate, due to the low level of prevailing sympathetic drive at night [21,22].…”
Section: Methodsmentioning
confidence: 99%
“…The long-term timedomain variable SDNN (representing total power in frequency domain) correlated best with scatterplot length and area (overall variation), while the short-term variables (rmsSD, pNNs0) strongly correlated with the scatterplot width (p90%) suggesting that this measure of variance should prove useful in assessing parasympathetic nervous activity [16]. These studies were undertaken during sleep; due to the low level of prevailing sympathetic drive at night, the agonist or antagonist activity of agents acting at the /31-or 32-adrenoceptor can be assessed from the sleeping heart rate [21,22]. Our study demonstrated that atenolol and propranolol did not increase scatterplot length or width, although this may have been due to the minimal sympathetic drive present during the night.…”
Section: Non-linear Analysis Of Heart Rate Variabil#y During Beta-adrmentioning
confidence: 98%
“…Previous studies in vivo have evaluated the P, and P2 components of PAA by measuring effects of single doses on resting parameters of heart rate, systolic blood pressure, tremor and forearm blood flow (McCaffrey et al, 1987(McCaffrey et al, ,1988. Such studies have not however, evaluated the effects of dose on the selectivity of PAA in vivo.…”
Section: Introductionmentioning
confidence: 99%